Intestinal parasitosis: Helminths: Prevalence and trend analysis between the years 2010 to 2017 in Peru - Vidal-Anzardo, Margot (2020)
Introduction. Helminth parasites cause nutritional, physical, and cognitive decline. The WHO has expressed the need to map the prevalence of parasites in Latin America and the Caribbean. In Peru there are no studies that have measured the prevalence of this pathology. Objectives. To determine the frequency of general parasitosis and by type of helminth in 2017 and the trend of the last 8 previous ones, years nationally and by department. Methods. Analysis of secondary database (Health Information System: HIS) from 2010 to 2017, which contains the record of care in health facilities of the Ministry of Health. For the analysis of trends, segmented regression models were used. Results. At the national level, general parasites and helminth parasites were 4,9% and 3,3%, respectively, in 2017; both presented a downward trend, decreasing each year by 8,8% and 11,3% respectively. The same occurred in 68% (17/25) of the regions, presenting a greater annual percentage reduction in Amazonas, Huánuco, La Libertad, Cajamarca and Huancavelica. Ascaris and enterobiasis occurred more frequently, each representing 0,3% in 2017. Conclusions. The prevalence of general parasitosis, by group of helminths and by specific type of helminths, is lower than that reported in other studies, which were carried out in the school population unlike this study, which was carried out in the general population where 57,2% were over 18 years of age who attended a health facility.